Accumulation of N, P, and K in the tubers of potato (iSolanum tuberosum/i L. ssp. iandigena/i) under contrasting soils of the Andean region of Colombia (2017)
The relationship between tuber growth and demand for NPK in andigena group of potato (Solanum tuberosum L. ssp. andigena) is poorly documented under conditions of the Andean region of Colombia. It is necessary to establish a specific nutrient management for high yields to changes in edaphicenvironmental supply and improve the production of Capiro and Supreme cultivars. Twelve treatments were evaluated at different stages (75-100-125-150 days after planting) of tuber growth using a repeated measures design with three factors: two cultivars (Capiro, Suprema); three locations with contrasting soils (Subachoque, Facatativa, and Choconta) and two levels of fertilization, F0 (unfertilized) and F1 (fertilized) of incomplete nature by differential fertilization by soil type. A positive correlation between fresh weight, dry weight and extraction of N, P and K (kg ha-1) by the tubers, beside harvest extraction index (HEI) was determined. Under optimal conditions of fertilization significant differences (P0.001) between factor interactions cultivar x phenology x location for accumulation of N and P were detected, where Suprema was less demanding in the HEI of N (1,92 kg t-1 harvest) and HEI of P (0.38 kg t-1 harvest) than Capiro and was better adapted to acid soils of low fertility, in contrast the HEI of K Between 5.28 and 5.34 kg t-1 harvest did not show differences between cultivars due to the genotypic characteristics in the accumulation of dry biomass and starch that make them suitable for industrial use, in addition it was verified that the nutritional extraction depends on the genetic potential determined by the interaction with the environmental and edaphic supply.